2019
DOI: 10.1177/2396987319841187
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic treatment for secondary prevention of stroke and other thromboembolic events in patients with stroke or transient ischemic attack and non-valvular atrial fibrillation: A European Stroke Organisation guideline

Abstract: Patients with ischemic stroke or transient ischemic attack and non-valvular atrial fibrillation have a high risk of recurrent stroke and other vascular events. The aim of this guideline is to provide recommendations on antithrombotic medication for secondary prevention of stroke and other vascular outcomes in these patients. The working group identified questions and outcomes, graded evidence, and developed recommendations according to the Grading of Recommendations Assessment, Development, and Evaluation appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
117
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 96 publications
3
117
0
4
Order By: Relevance
“…In RCT subanalyses that compared the efficacy and safety of NOACs against VKA, it was not shown that the use of NOACs has a different effect in the elderly population compared to younger people (17)(18)(19). The ESO Guideline gives preference to NOACs over VKA in the elderly population, although there is currently no data on whether there are differences between older and younger patients with previous IS and AF (22).…”
Section: The Noacs In Specific Groups Of Patients With Previous Is Anmentioning
confidence: 99%
See 3 more Smart Citations
“…In RCT subanalyses that compared the efficacy and safety of NOACs against VKA, it was not shown that the use of NOACs has a different effect in the elderly population compared to younger people (17)(18)(19). The ESO Guideline gives preference to NOACs over VKA in the elderly population, although there is currently no data on whether there are differences between older and younger patients with previous IS and AF (22).…”
Section: The Noacs In Specific Groups Of Patients With Previous Is Anmentioning
confidence: 99%
“…The introduction of OAC in these patients should consider the degree of cognitive decline, ability to understand, quality of life and life expectancy, the possibility of poor therapeutic adherence, and higher risks of hemorrhagic complications. The ESO Guideline gives preference to NOACs over VKA in the secondary prevention of IS in patients with AF and cognitive deficits (22).…”
Section: The Noacs In Specific Groups Of Patients With Previous Is Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, current guidelines emphasize prolonged cardiac rhythm monitoring for AF in cryptogenic stroke [14][15][16][17]. However, prolonged cardiac rhythm monitoring (a minimum of 24 hours) for AF are not usually used as recommended in clinical practice.…”
Section: Introductionmentioning
confidence: 99%